ANTECEDENTS OF CUSTOMER LOYALTY : DOES SERVICE QUALITY SUFFICE? - K, Kiran; S, Diljit (Malaysian Journal of Library and Information Science, 2017)
This study reports on an investigation of the antecedents of customer loyalty in an academic library setting. A structural model is presented to test the relationships between web-based library service quality, service value, customer satisfaction and customer loyalty based on theoretical underpinnings in the literature on service quality and customer loyalty. The study provides empirical data on library users’ behavioral intentions, which helps understand the nature of customers’ loyalty towards web-based library services. Participants included postgraduates and academic staff from four research intensive universities in Malaysia. Structural equation modeling was carried out to test the modeled relationships between the four construct in this study. This study provides insights into the antecedents of customer satisfaction and customer loyalty as findings revealed that service quality and service value have a direct effect on customer satisfaction, which then directly impacts customer loyalty.